Role of food contact materials in the safety assessment of potentially hazardous substances and in the dietary exposure of infants - Brigitte Dittmann; Petra Schmid; Diana Kemmer (Global Pediatrics, 2022)
The largest application area of food contact materials is the packaging of foodstuff, being an essential element in the preservation of the microbiological and sensory quality of the packaged goods. However, chemical compounds present in the packaging material, either intentionally added or non-intentionally present, may migrate into the food during packaging and storage. With a large variety of materials used in the production, food packaging requires safety assessments with respect to the migration of packaging compounds into the packaged goods. The present article deals with the safety assessment of potential migrants from food contact materials, approaches to migration testing and summarizes European food regulatory requirements with special focus on infants’ dietary exposure.